Interculturalism and Performance Now
XXII, 377 p. 18 illus.
Keywords: This book is the first edited collection to respond to an undeniable resurgence of critical activity around the controversial theoretical term ‘interculturalism’ in theatre and performance studies. Long one of the field’s most vigorously debated concepts, intercultural performance has typically referred to the hybrid mixture of performance forms from different cultures (typically divided along an East-West or North-South axis) and its related practices frequently charged with appropriation, exploitation or ill-founded universalism. New critical approaches since the late 2000s and early 2010s instead reveal a plethora of localized, grassroots, diasporic and historical approaches to the theory and practice of intercultural performance which make available novel critical and political possibilities for performance practitioners and scholars. This collection consolidates and pushes forward reflection on these recent shifts by offering case studies from Asia, Africa, Australasia, Latin America, North America, and Western Europe which debate the possibilities and limitations of this theoretical turn towards a ‘new’ interculturalism. .